IDENTIFIKASI IDENTIFIKASI PENGETAHUAN MASYARAKAT TENTANG PERILAKU HIDUP BERSIH DAN SEHAT DALAM UPAYA PENCEGAHAN PENULARAN COVID-19 - alvin abdillah; kurniati prihatin; Marthuilda Suprayitna (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2021)
The health problem that is currently in the spotlight and attention of the world is the Covid-19 disease. The best way to control and prevent disease is to break the chain of the spread of COVID-19. Every individual in the family participates in various efforts to overcome or break the chain of the spread of this pandemic. Knowledge of clean and healthy living behavior (PHBS) is essentially the basis for preventing humans from various diseases. The purpose of this study was to identify public knowledge about clean and healthy living behavior in an effort to prevent the transmission of COVID-19. This research method uses a descriptive method with a cross sectional design approach. Sampling was done by purposive random sampling technique with a population of 312 people with a sample of 77 people. Results and suggestions: the results of the study showed that the knowledge of the community with clean and healthy living behavior as an effort to prevent the transmission of covid-19 was mostly in the less category, namely as many as 64 respondents (83.1%). It is hoped that the public will pay more attention to and increase knowledge about clean and healthy living behavior as an effort to prevent the transmission of COVID-19. Keywords: Knowledge; PHBS; Covid-19.